Local Anesthetics, Clinical Uses, and Toxicity: Recognition and Management - Ozbay, Sedat; Ayan, Mustafa; Karcioglu, Ozgur (Current Pharmaceutical Design, 2023)
Local anesthetic (LA) compounds decrease the permeability of the ion channels to sodium, which in turn, reduces the rate of depolarization. These agents (a.k.a. -caines) are also used to depress mucosal sensations, e.g., gag reflex in the form of topical anesthetics. Overdose of LA can lead to local anesthetic systemic toxicity (LAST), which is the precursor of potentially lethal consequences on clinical grounds. There is a wide array of possible presentations of LAST, from mild findings, such as temporary hypertensive events, to serious conditions, including refractory cardiac dysfunction, dysrhythmias and prearrest situations. Lidocaine, prilocaine, mepivacaine, ropivacaine, and bupivacaine are among the most commonly used members of the family. The agents’ dosages should be adjusted in children, elderly and fragile individuals and those with organ failures, as the metabolism of the compounds will be impaired. The ideal body weight, along with hepatic and renal functional reserves, will have an impact on elimination kinetics. Systemic absorption is an untoward consequence of LA administration which deserves every means of prevention. Intravenous lipid emulsion is an important life-saving treatment in severe, life-threatening cases. This narrative review article is designed to cover the clinical uses of LA in children, recognition, and management of untoward effects of the agents, with special emphasis on the LAST.
Keywords: children